Tinjauan Kelengkapan Rekam Medis Rawat Inap di Rumah Sakit Umum Daerah Kembangan - Nabilah Khairunisa; Dina Sonia; Puteri Fannya; Noor Yulia (Yayasan Literasi Sains Indonesia, 2023)
The completeness of filling in the medical record can be checked using a documentation audit, one of which is quantitative analysis by reviewing certain parts of the contents of the medical record with the intention of finding deficiencies, especially those related to medical record documentation. The purpose of this study was to get an overview of the completeness of filling out inpatient medical records at the Kembangan Regional General Hospital. This research method uses a descriptive method with a quantitative approach. The population in this study were inpatient medical records at the Kembangan Regional General Hospital with a sample of 89 medical records. Based on the results of calculations using quantitative analysis obtained an average completeness of 82%, the highest completeness is the patient identification component of 87% and the lowest completeness is the important reporting component of 76%. Based on the research that has been done, it can be concluded that filling in the medical record at the Kembangan Regional General Hospital is not complete, this is due to the lack of awareness of health workers to complete filling in the medical record so that it has an impact on incomplete filling in medical record files